Evaluasi dan optimalisasi sistem informasi akuntansi pencatatan dan pelaporan keuangan pembayaran SPP Siswa di SMK Taman Wisata Cileungsi: Menuju sistem yang lebih efisien dan efektif - Amalia, Fathia Nur; Indarsari, Aisyah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
This study aims to create a more efficient and effective system, focusing on the accounting system for recording and reporting student tuition payments at SMK Taman Wisata Cileungsi. The goal is to analyze the implementation of the current accounting system. The method used is a qualitative approach, where the researcher serves as the main instrument. Data collection was carried out purposively and snowball, with triangulation as a data collection technique, and qualitative analysis that emphasizes meaning rather than generalization. Based on observations, SMK Taman Wisata Cileungsi is one of the Private Vocational High Schools in Cileungsi that still uses a manual system for recording and reporting tuition payments, although the data is backed up automatically at the end of each day. One source stated that "the data stored is very safe in the system." The conclusion of the study shows that evaluation and optimization of the accounting information system are needed to improve efficiency and effectiveness in recording and reporting student tuition payments, by identifying several problems, such as data inaccuracy, length of processing time, and difficulty in accessing information.